2010
DOI: 10.1051/vetres/2010012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of canine monocyte- and bone-marrow-derived dendritic cells

Abstract: Dendritic cells (DC) represent a heterogeneous cell family of major importance for innate immune responses against pathogens and antigen presentation during infection, cancer, allergy and autoimmunity. The aim of the present study was to characterize canine DC generated in vitro with respect to their phenotype, responsiveness to toll-like receptor (TLR) ligands and T-cell stimulatory capacity. DC were derived from monocytes (MoDC) and from bone marrow hematopoietic cells cultured with either Flt3-ligand (FL-BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…The higher CD11c expression in BM-MΦs was somewhat surprising but may be due to the fact that BM-MΦs in these studies were identified exclusively based on adherence characteristics in culture conditions that are DC-promoting (i.e. GM-CSF) but do not necessarily inhibit macrophage differentiation (Lutz et al, 1999; Ricklin Gutzwiller et al, 2010). At present, definitive generation of canine BM-MΦs is limited by a lack of recombinant canine M-CSF, a growth factor that generates macrophages.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The higher CD11c expression in BM-MΦs was somewhat surprising but may be due to the fact that BM-MΦs in these studies were identified exclusively based on adherence characteristics in culture conditions that are DC-promoting (i.e. GM-CSF) but do not necessarily inhibit macrophage differentiation (Lutz et al, 1999; Ricklin Gutzwiller et al, 2010). At present, definitive generation of canine BM-MΦs is limited by a lack of recombinant canine M-CSF, a growth factor that generates macrophages.…”
Section: Discussionmentioning
confidence: 88%
“…Adherence and morphologic characteristics of DH82 cells in culture are similar to the DC cell line DC2.4, and GM-CSF treatment generated BM-DCs in mice and dogs (Lutz et al, 1999; Papenfuss, 2010, unpublished observations; Shen et al, 1997). Unlike in mice, a single individual marker such as CD11c or CD1c does not exclusively identify DC populations or differentiate these from monocytes or macrophages (Ricklin Gutzwiller et al, 2010). For our studies, we compared CD11c, CD11b and MHC class II expression between three myeloid cell populations and found that BM-DCs expressed similar CD11c, CD11b and MHC class II levels as DH82 cells, which differed from expression patterns in BM-MΦs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD206-encoding gene is conserved from birds to mammals (Staines et al 2014); however, we have little information on the macrophage expression of CD206 outside of rodents. Equine myeloid cells express CD206 (Steinbach et al 2005) and dog CD206 expression (Gene ID: 487114) has been reported in in vitro differentiated macrophages and in bone-marrow-derived dendritic cells (Ricklin Gutzwiller et al 2010). One excretory product of the canine parasite Toxocara canis, which helps evade host defense and allows survival in the tissues, has a sequence similarity to CD206 (Loukas et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A redução da atividade fagocítica com o processo de maturação foi descrita por Sallusto et al (1995) Assim como os humanos e roedores, a atividade aloestimulatória em cães pode ser realizada por meio do co-cultivo das DCs com linfócitos, seguido pela medição da proliferação celular realizada por meio da incorporação do CFSE-DA aos linfócitos e avaliação da divisão celular por citometria de fluxo (WIJEWARDANA et al, 2006;WANG et al, 2007b;GUTZWILLER et al, 2010).…”
Section: Caracterização Fenotípicaunclassified